2021
DOI: 10.7819/rbgn.v23i4.4130
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making under Ignorance and Product Disclosure: Implications in Buying Insurance

Abstract: Purpose -The subject of making choices under risk has been studied based on the assumption that decision makers are fully informed. However, in real life situations individuals frequently need to make choices without the benefit of essential information. This study analyzes decision making in the absence of information about the probabilities of losses and potential impacts, which constitutes a context of ignorance, or alternatively making choices under risk or uncertainty.Theoretical framework -This study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In this way, satisfactory insurance services can increase their trust in financial knowledge, financial products, and financial talents. As Mendes-Da-Silva, et al [7] found, in the context of risk and uncertainty, a lack of economic information and insufficient information disclosure increase the insurance costs of consumers, while reducing the intention to buy insurance. Supported by digital technology, the appropriate disclosure of financial information and popularization of financial knowledge can promote the financial literacy of the middle-aged and elderly and help them understand the content and role of IMI with less time and money cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, satisfactory insurance services can increase their trust in financial knowledge, financial products, and financial talents. As Mendes-Da-Silva, et al [7] found, in the context of risk and uncertainty, a lack of economic information and insufficient information disclosure increase the insurance costs of consumers, while reducing the intention to buy insurance. Supported by digital technology, the appropriate disclosure of financial information and popularization of financial knowledge can promote the financial literacy of the middle-aged and elderly and help them understand the content and role of IMI with less time and money cost.…”
Section: Discussionmentioning
confidence: 99%
“…According to Mendes-Da-Silva, et al [7], the abundance and disclosure of economic information play an important role in the propensity to purchase insurance. Dragos, et al [8] divided economic behaviour into general financial behavioural variables and insurance-specific behavioural variables.…”
Section: Introductionmentioning
confidence: 99%